Non-coding RNAs Potentially Controlling Cell Cycle in the Model Caulobacter crescentus: A Bioinformatic Approach - Beroual, Wanassa; Brilli, Matteo; Biondi, Emanuele G. (Frontiers in Genetics, 2018)
Caulobacter crescentus represents a remarkable model system to investigate global regulatory programs in bacteria. In particular, several decades of intensive study have revealed that its cell cycle is controlled by a cascade of master regulators, such as DnaA, GcrA, CcrM and CtrA, that are responsible for the activation of functions required to progress through DNA replication, cell division and morphogenesis of polar structures (flagellum and stalk). In order to accomplish this task, several post-translational (phosphorylation and proteolysis) and transcriptional mechanisms are involved. Surprisingly, the role of non-coding RNAs (ncRNAs) in regulating the cell cycle has not been investigated. Here we describe a bioinformatic analysis that revealed that ncRNAs may well play a crucial role regulating cell cycle in C. crescentus. We used available prediction tools to understand which target genes may be regulated by ncRNAs in this bacterium. Furthermore, we predicted whether ncRNAs with a cell cycle regulated expression profile may be directly regulated by DnaA, GcrA and CtrA, at the onset, during or end of the S-phase/swarmer cell, or if any of them has CcrM methylation sites in the promoter region. Our analysis suggests the existence of a potentially very important network of ncRNAs regulated by or regulating well-known cell cycle genes in C. crescentus. Our hypothesis is that ncRNAs are intimately connected to the known regulatory network, playing a crucial modulatory role in cell cycle progression.